Análise experimental do desempenho de um trocador de calor do tipo casco e tubos - Ferreira, Cassio Eduardo Nadal (2014)
In this Work Course Conclusion an experimental investigation of shell and tube heat exchanger performance under different operating conditions in counter flow and parallel flow was performed. The heat transfer rate in different settings was found by three different methods: Energy Balance, Average logarithmic differences of temperatures (MLDT) and Effectiveness-NUT (ε-NUT). Experimental tests were performed on an experimental apparatus located in Educational Laboratory of Thermal Science of Academic Department of Mechanical, Federal Technological University of Paraná/Ponta Grossa. The technical specifications of Shell and tubes heat exchanger are: Shell Type E, front head Type A, end head Type L, tube bundles in fixed array of 90 ° and single-segmental baffles. The experimental uncertainties were calculated using the Simple Sampling technique with the support of Uncertainty Calculator software. The thermophysical properties of the fluid and the tubes were obtained from the Engineering Equation SolverTM (EESTM) software library. The experimental results of the performance of heat exchangers, indicated that the highest heat transfer rates occur for higher flow rates of hot and cold fluids and larger temperature gradients between the inlet hot and cold fluids. For the same conditions of inlet temperature and flow of hot and cold fluids flow in countercurrent configuration showed higher rates of heat transfer between the fluids.